Effect Endorphin Massage on Anxiety Labor Levels of First Stage - Anis Nikmatul Nikmah; Dhita Kris Prasetiyanti; Eko Winarti; Karima Meireza; Hiromi Ogasawara (Journal Of Nursing Practice, 2022)
Background: Endorphin massage stimulates the body to release endorphin compounds; these hormones can create a sense of comfort thereby reducing anxiety. Purpose: The purpose of this study was to prove the effect of endorphin massage on the anxiety level of the first stage of maternal I. Pre-experimental research design with one group pretest-posttest design. The population of all mothers in childbirth I. Methods: The sample size was 16 respondents, the accidental sampling technique. Data collection uses observation sheets. Endorphin massage by the husband for 10 minutes, massage performed for 20 minutes in 1 hour and every 10 minutes in 30 minutes at the time of contraction. Data analysis using paired t test. Results: The results showed that before giving endorphin massage, the average respondent experienced severe anxiety (30.00). Whereas after being given an endorphin massage the average respondent experiences moderate anxiety (26,19). The value of p = 0,000 is the effect of endorphin massage on the level of anxiety of the first stage of labor. Conclusion: Massage through the skin surface during labor will improve the relaxed condition in the body so that it triggers a feeling of comfort.